Айтыстағы шешендіктің қызметі - Əбдуов, М.І.; Қуанбаева, Д. (ҚарМУ баспасы, 2011)
Статья, посвященная сравнительному анализу особенностей ораторской речи биев и айтыскеров, является актуальной сегодня, так как ранее их ораторское искусство было всестронне исследовано по отдельности. Автором делается попытка раскрыть своеобразие некоторых граней искусства биев с точки зрения употребления лексики и влияния на художественность образного строя и высокий уровень использования айтыскерами языковых форм. Article is devoted to the comparative analysis of features of an oratorical speech and aitys players. For today there was not ivestigated the oratorical speech and aitys player’s creativity in the given aspect because a detailed research each of them has been connected with their studying separately. In article there is attempted to open an originality of some sides of oratorical art from the point of view of the use of lexicon and its influence on artistry of image system and a high level of use of a language forms is done.